(untitled) (The Review of Diabetic Studies, 2025)
The advancement of green chemical manufacturing depends on the creation of sustainable catalytic systems. In contrast to commercial Pd/C catalysts, colloidal palladium nanoparticles supported on carbon (Pd/C) were synthesized in this study using a controlled colloidal route to increase activity, selectivity, and recyclability. In contrast to the heterogeneous particle sizes (7–18 nm) seen in conventional systems, transmission electron microscopy verified uniform nanoparticle dispersion with an average diameter of 3.8 ± 0.5 nm. In the Suzuki–Miyaura cross-coupling reaction, catalytic testing consistently produced high yields of 92–95.4%, while commercial Pd/C yielded 78.6% ± 3.1%. With selectivity above 95% and byproduct formation limited to ≤3%, the colloidal Pd/C demonstrated a turnover frequency (TOF) of 3,450 h⁻¹, a 68% increase over the reference catalyst. After five cycles, recycling tests showed that 85.7% of the initial activity was still present, while conventional Pd/C only retained 61.2%. Greater durability was highlighted by the colloidal system’s low Pd leaching (0.8 ppm, <0.02%) as opposed to the reference’s 3.5 ppm ( 0.1%). The colloidal catalyst’s sustainability was further reinforced by green metrics. Atom economy increased to 82%, the process mass intensity (PMI) improved from 1.65 to 1.18, and the E-factor decreased from 12.0 to 7.2 (a 40% reduction in waste). Furthermore, the efficiency of solvent recovery was higher (92% vs. 78%). These results show that colloidal Pd/C is a promising system for sustainable transition metal catalysis since it not only increases catalytic efficiency but also greatly improves environmental performance.